Revealing the Evolution Processes of Excitons on High Energy Level in Anthracene‐Based OLEDs. (20th August 2022) - Xiao, Shu; Qiao, Xianfeng; Lin, Chengwei; Li, Yuanzhao; Ying, Shian; Qin, Jianwen; Guo, Runda; Wang, Lei; Ma, Yuguang; Ma, Dongge
Abstract: It is well‐known that the electrically generated excitons can perform the spin evolution between high‐lying excited states, providing an efficient way to utilize triplet excitons in organic light‐emitting diodes (OLEDs). Anthracene families offer an opportunity to deeply investigate the processes of triplet excitons on high‐lying excited states in detail. Here, a simplified model is proposed to study the exciton dynamics in anthracene derivatives‐based devices. The mechanism on the processes of high‐energy level intersystem crossing in anthracene derivatives is well revealed by theoretical calculation, transient electroluminescence, transient photoluminescence, and transient absorption spectrum measurements. Besides, doping strategy is proposed to suppress the exciton loss channel for improving the efficiency of devices. The studies establish an in situ method to evaluate the apparent singlet exciton formation ratio in devices due to the exciton evolution between high‐lying excited states and offer some clues to further utilize these triplet excitons, thus improving the efficiency of the resulting fluorescence OLEDs in the future. Abstract : The conversion between excitons on high energy level offers the opportunity of improving the efficiency of organic light‐emitting diodes. However, the device physics is still unclear. Anthracene families offer an opportunity to deeply investigate the processes of triplet excitons on high‐lying excited states in detail due to the satisfied energy level matching of both triplet–triplet up‐conversion and high‐lying charge‐transfer state.